2015
DOI: 10.1093/jme/tjv069
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro and In Vivo Evaluation of Infestation Deterrents Against Lice

Abstract: The human head louse is a cosmopolitan ectoparasite and frequently infests many people, particularly school-age children. Due to widespread pyrethroid resistance and the lack of efficient resistance management, there has been a considerable interest in the protection of uninfested people and prevention of reinfestation by disrupting lice transfer. In this study, two nonclinical model systems (in vitro and in vivo) were used to determine the efficacy of the infestation deterrents, Elimax lotion and Elimax shamp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 33 publications
0
2
0
1
Order By: Relevance
“…External parasites, most likely Menopon spp. and Menacanthus spp., based on their location and previous studies 35 ( Supplementary Fig. 1A, 1B), were seen on 60 chickens (74%), although 5 chickens had feather loss.…”
Section: Postmortem Examinationmentioning
confidence: 58%
“…External parasites, most likely Menopon spp. and Menacanthus spp., based on their location and previous studies 35 ( Supplementary Fig. 1A, 1B), were seen on 60 chickens (74%), although 5 chickens had feather loss.…”
Section: Postmortem Examinationmentioning
confidence: 58%
“…In this study, no differences in the death odds-ratios were identified. All odds-ratios were combined to a single value and tested using the Cochran-Mantel-Haenszel (CMH) test statistic for comparing the odds of death for homozygous and heterozygous resistant genotypes [ 23 , 24 ]. The impact of the factors, area, genotype, distance and cage on the probability of survival of the mosquitoes was assessed through a logistic regression model.…”
Section: Methodsmentioning
confidence: 99%
“…Los piojos, como cualquier forma de vida que evoluciona, desarrollan sofisticados mecanismos de resistencia contra los pediculicidas, los cuales heredan a las nuevas generaciones de insectos. Dicho fenómeno se agudiza por la falta de un manejo eficiente de estos medicamentos, razón por la cual en muchos países se están realizando estudios que confirman la creciente resistencia de P. capitis (55,56…”
Section: Resistencia a Los Pediculicidasunclassified